Design and optimization of permanent magnet machine for ceiling fan - Zulkarnain, N.F. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents an analysis on the optimization of the permanent magnet synchronous machine (PMSM) with the implementation of the single rotor double stator that comprises two systems in one machine, the motor and the generator. This machine was developed for ceiling fan application to increase the efficiency of the system. The five optimization designs have different split ratio and pole pitch ratio and Finite Element Analysis (FEA) has been performed to predict the performance of the designs by analyzing the open circuit flux distribution, air gap flux density and the back EMF. The optimal value of the split ratio is identified to be 0.52 and the pole pitch ratio is 0.5. The split ratio simulation verified that the flux distribution, air gap flux density and the back EMF are affected by the air gap radius. On the other hand, the pole pitch ratio optimization analysis proved that the average value of back EMF is decreasing and the flux distribution of the air gap is fluctuated as the arc length angle between the North-pole and South-pole is unbalanced. Overall, good achievement was achieved. © 2016 IEEE.